RECONSTRUCTION OF MECHANISMS REGULATING THE EXPRESSION OF THE ESCHERICHIA COLI YFIA GENE UNDER STRESS CONDITIONS - T. M. Khlebodarova; D. Yu. Oshchepkov; N. V. Tikunova; I. V. Babkin; A. D. Gruzdev; V. A. Likhoshvai (Вавиловский журнал генетики и селекции)
The regulatory region of the Escherichia coli yfiA gene was reconstructed by using the SiteCon web resource and mathematical modeling, and its expression complexity under oxidative stress was assessed. Simulation of the response of E. coli cells transformed with pYfi-gfp plasmid to oxidative stress indicated that the maximum agreement with experimental data was achieved in a model implying a complex action, apparently mediated by several transcription factors (TFs). The regulatory region of the yfiA gene was searched for potential TF binding sites, and highly reliable recognition was predicted for TFs MarA, IscR, MetJ, PurR, and SoxS, which directly or indirectly participate in the response of the gene to oxidative stress, and for CRP, a global regulator of carbohydrate catabolism. The presence of binding sites for CRP, MarA, and SoxS in the E. coli yfiA promoter was confirmed by electrophoretic mobility shift assay with purified recombinant TFs. This fact explains the sensitivity of yfiA to mitomycin and radical-forming agents.